PENGARUH PENERAPAN MODEL PEMBELAJARAN HUMANIZING THE CLASSROOM DALAM MENINGKATKAN HASIL BELAJAR SISWA - Vuvut Budi Saputri; Muh Misdar; Muhamad Fauzi (PAI RAFAH, 2022)
In the learning process, it was seen that some students were passive, and some students' learning outcomes were low. The purpose of this study, namely, to find out how the learning outcomes of class VII A students as a control class in fiqh subjects at Mts Ahliyah I Palembang, to find out how the learning outcomes of class VII B students as an experimental class at Mts Ahliyah I Palembang, to find out whether there is an effect of applying the humanizing the classroom learning model between control and experimental classes in improving student learning outcomes at Mts Ahliyah I Palembang. This research uses quantitative research. The type of research used is Pre-experimental research designs from Two group postest-only designs. The data sources used are primary data and secondary data. This type of research uses data collection methods used are observation, tests, and documentation. The data analysis technique uses the t-test formula. The results of the analysis there is a difference between the control class and the experimental class n at MTs Ahliyah I Palembang, this can be seen from the results of calculations with the t-test formula on the test questions given show that t_0 has been obtained equal to 3.809 while t_t = 2.064 and 2.797 then t_o is greater than t_t both at a significant level of 5% and a significant level of 1% thus H_a is accepted and Ho is rejected. Thus it can be concluded that there is a significant difference in the effect of applying the Humanizing The Classroom model.